Effect of length and diameter of fiber reinforced composite post (FRC) on fracture resistance of remaining tooth structure - Mahdiyeh seifi; Bijhan Heidari; Nafiseh Asadzadeh Aghdaee; Saeid Ebrahimzadeh (Mashhad University of Medical Sciences, 2013)
Introduction: Post and core has been considered for endodontically treated tooth, especially in cases with severe damage crowns. Recently fiber reinforced composite posts (FRC post) have been used in the treatment of endodontically treated teeth. Because the length and diameter of posts are effective in stress distribution, the purpose of this study is to evaluate the effect of length and diameter of FRC post on fracture resistance. Methods: In this experimental study, 36 glass fiber posts with combination of 7mm, 9mm, and 12mm length and 1.1mm, 1.3mm and 1.5mm diameter were divided into 9 groups of 4. These posts were cemented in root canals by Panavia. Samples were tested with 45° compressive forces for the evaluation of fracture resistance. Datas were analyzed using SPSS soft ware and One- way and Two-way ANOVA analyses. Results: Fracture resistance did not increase significantly with the effect of length and diameter simultaneously (P=0.85). Samples with 12mm length and 1.5mm diameter had the greatest fracture resistance (1023/33N±239/22). The minimum fracture resistance had occurred in post with 7mm length and 1.5mm diameter (503/13N ±69/18). Fracture resistance increased significantly by increasing the length and the same diameter. Conclusion: It can be concluded that fracture resistance is affected by the length and not the diameter of FRC post.